Studies on water mites of the family Hygrobatidae (Acari, Hydrachnidia) from Iran, I. The water mite genus Atractides Koch, with the description of five new species - Pesic, Vladimir; Saboori, Alireza; Asadi, Mahdieh; Vafaei, Reza (Zootaxa, 2004)
This survey of the distribution of the water mite species (Acari: Hydrachnidia, Hygrobatidae) of the genus Atractides Koch in Iran is based on all published data so far and numerous new records. Five new species are described, viz. Atractides markaziensis Pesic, A. mossahebii Pesic, A. mirkopesici Pesic, A. gereckei Pesic, and A. nikooae Pesic; a first description is given for the male of Atractides cf. lunipes Lundblad, 1956; a redescription are given for Atractides baderi Schwoerbel & Sepasgozarian, 1976, Atractides nahavandii Schwoerbel & Sepasgozarian, 1976, and Atractides fluviatilis (Szalay, 1929); first records from Iran are given for Atractides acutirostris (Motas & C.Angelier, 1927), A. robustus (Sokolow, 1940) and A. inflatus (Walter, 1925).